Hotel management / Samsudin Md. Yusof - Md. Yusof, Samsudin (Faculty of Architecture, Planning and Surveying, 1982)
Management can be defined either as a group of people or as a process. When referring to a group of people, the word describes those individuals who are responsible for coordinating the available resources and directing them toward the achievement of the predetermined goals and objectives. In the most limited sense of the word, only those individuals who occupy the highest rungs of the organizational ladder are referred to as management. However, we now find that many theorists and practitioners are advocating the idea that all of the individuals within an operation are managers with respect to their specific areas. The dishwasher can be taught to manage the operation and maintenance of his machine, while the waiters and waitresses can be directed to manage their stations as well as the presentation and serving of the meal.